First Lady Chatterley - Lawrence, D. H. (Dial Press New York, 1944)
This is the first version of three written by D. H. Lawrence. It is in sharp contrast to the Lady Chatterley's Lover, which dwindles to a tract on sex and a fantasy of wish-fulfillment. It version is a full-fledged work of art, presenting the difficulty in close human contact between individuals and between classes.
Keywords: Gothic Romance; Sexual Relationships; Adultery